2011
DOI: 10.1620/tjem.224.111
|View full text |Cite
|
Sign up to set email alerts
|

Human t-Complex Protein 11 (TCP11), a Testis-Specific Gene Product, Is a Potential Determinant of the Sperm Morphology

Abstract: Fertilization promoting peptid (FPP) is essential for capacitation and acrosome reaction. The mouse t-complex protein 11 (Tcp11) gene, which encodes the receptor of FPP, plays an important role in fertilization. We had identified three alternative splicing products of its human homologous gene, TCP11, nominated as TCP11a, TCP11b and TCP11c. Their testis-specific expression had been noted, suggesting that TCP11 may play an important role in spermatogenesis and sperm function. In order to explore the function of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“… [ 81 ] Q8WWU5 TCP11 T-complex protein 11 homolog isoform 1 Fertile group only May play an important role in sperm function and fertility. [ 82 , 83 ] Q8WYR4 RSPH1 Radial spoke head 1 homolog May play an important role in male meiosis. [ 84 , 85 ] Q96A08 HIST1H2BA Histone H2B type 1-A Variant histone specifically required to direct the transformation of dissociating nucleosomes to protamine in male germ cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… [ 81 ] Q8WWU5 TCP11 T-complex protein 11 homolog isoform 1 Fertile group only May play an important role in sperm function and fertility. [ 82 , 83 ] Q8WYR4 RSPH1 Radial spoke head 1 homolog May play an important role in male meiosis. [ 84 , 85 ] Q96A08 HIST1H2BA Histone H2B type 1-A Variant histone specifically required to direct the transformation of dissociating nucleosomes to protamine in male germ cells.…”
Section: Resultsmentioning
confidence: 99%
“…May help to maintain the passive elastic structures and elastic recoil of the sperm tail. [ 73 , 83 , 87 ] Q96QH8 SPACA5 Sperm acrosome-associated protein 5 precursor Fertile group only Sperm acrosome-associated protein 5. [ 88 ] Q99497 PARK7 Protein DJ-1 It acts as atypical peroxiredoxin –like peroxidase that scavenges hydrogen peroxide.…”
Section: Resultsmentioning
confidence: 99%
“…The level of expression of TCP11 (human y‐complex protein 11) is 70% less in samples containing high rates of spermatozoa with coiled tails (Liu et al ., ). Their results show that TCP11 interacts with ODF1 (a major component of outer dense fibers) that plays a role in flagellar morphogenesis.…”
Section: Resultsmentioning
confidence: 97%
“…The human genome also encodes homologs of the other identified SPIF complex proteins: TCP11 and PRKACA2. It has been demonstrated that Tcp11 is not expressed in the testes of some patients with azoospermia (49), and expression is reduced in the sperm of males with poor morphology (50). It will be interesting to extend this study into human samples and assess the role of the SPIF/TCP11/PKAC complex in human capacitation and fertility.…”
Section: Discussionmentioning
confidence: 99%